Quasi-targeted metabolomics revealed isoliquiritigenin and lauric acid associated with resistance to tobacco black shank - Shiwen Peng; Fangling Shu; Yanhui Lu; Dongsheng Fan; Dehong Zheng; Gaoqing Yuan (Plant Signaling & Behavior)
Tobacco black shank (TBS), caused by Phytophthora nicotianae, is a severe disease. Plant root exudates play a crucial role in mediating plant-pathogen interactions in the rhizosphere. However, the specific interaction between key secondary metabolites present in root exudates and the mechanisms of disease resistance remains poorly understood. This study conducted a comprehensive comparison via quasi-targeted metabolomic analysis on the root exudate metabolites from the tobacco cultivar Yunyan87 and K326, both before and after inoculation with P. nicotianae. The results showed that the root exudate metabolites changed after P. nicotianae inoculation, and the root exudate metabolites of different tobacco cultivar was significantly different. Furthermore, homovanillic acid, lauric acid, and isoliquiritigenin were identified as potential key compounds for TBS resistance based on their impact on the mycelium growth of the pathogens. The pot experiment showed that isoliquiritigenin reduced the incidence by 55.2%, while lauric acid reduced it by 45.8%. This suggests that isoliquiritigenin and lauric acid have potential applications in the management of TBS. In summary, this study revealed the possible resistance mechanisms of differential metabolites in resistance of commercial tobacco cultivar, and for the first time discovered the inhibitory effects of isoliquiritigenin and homovanillic acid on P. nictianae, and attempt to use plants secondary metabolites of for plant protection.